Intelligent Agents in the Evolution of Web and Applications - Nguyen, Ngoc Thanh (Springer, 2017)
Intelligent agents have revolutionised the way we do business, we teach, we learn, design systems, and so on. Agent applications are increasingly being developed in - mains as diverse as meteorology, manufacturing, war gaming, UAV mission mana- ment and the evolution of Web [1]. The Web has also has the same effect on our daily life as the intelligent agents. We use Web for information search, shopping, news, communication and so on. We wonder how we lived without Web in the past [2]. The book presents a sample of some of the most innovative research on the use of intelligent agents in the evolution of Web. There are thirteen chapters in the book. Chapters are on theoretical foundations as well as practical applications. We are grateful to the contributors and reviewers for their contribution. We believe that the research reported in the book will encourage researchers to develop the robust human-like intelligent machines for the service of humans. We sincerely thank Springer-Verlag for their editorial support during the prepa- tion of the manuscript. The editors appreciate the resources provided by Wroclaw University of Technology and the University of South Australia to edit this volume.